PHASE METHODS OF GAS GENERATORS CONTROL HYDROGEN STORAGE AND SUPPLY SYSTEMS: Array - Abramov, Y.; Kryvtsova, V.; Mikhailyuk, A. (Municipal economy of cities (Technical science), 2021)
Methods of control of technical condition of gas generators of systems of storage and supply of hydrogen based on use of their phase-frequency characteristics are considered. Methods of control of gas generators are divided into two groups depending on the mathematical models used to describe the operation of such gas generators. It is shown that when using as such a mathematical model the transfer function of the gas generator in the form of an inertial link, it is possible to implement control algorithms both by its phase-frequency characteristics and by its time constant. In the first case, the phase-frequency characteristic is measured at an a priori set frequency. In the second case, there is no such restriction. When using as a mathematical model of the gas generator the transfer function in the form of a fractional-rational function of the second order, the implementation of algorithms for its control can be carried out directly using the phase-frequency characteristics of the gas generator. With this implementation of algorithms for monitoring the technical condition of gas generators, the measurement of the values of their phase-frequency characteristics is carried out at several frequencies. This approach to the control of gas generators can increase the reliability of its results. All methods of monitoring the technical condition of gas generators of hydrogen storage and supply systems are focused on the use of tolerance criteria. The parameters of the tolerance criteria can be both the values of the time constants of gas generators of hydrogen storage and supply systems, and fixed values of the phase-frequency characteristics of such gas generators. In the latter case, control algorithms are implemented that cover the entire operating frequency range of gas generators.